1969
DOI: 10.1002/anie.196906751
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Ynamines with Iminium Salts

Abstract: Bis(N4luorosulfonylimido)sulfur difluoride [21 ( I ) reacts with dimethylamine in diethyl ether to give dimethylamidobis-(N-fluorosulfony1imido)sulfur fluoride (2). Dimethylamine (6.8 g, 0.15 mole) is passed into a stirred solution of ( I ) (18.5 g, 0.07 mole) in diethyl ether (300 ml) at -78 "C during 1 h. The reaction mixture is then warmed to room temperature and the ethereal phase separated off. Removal of the ether under reduced pressure and subsequent distillation of the residue at oil-pump vacuum afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This study also demonstrated that a broad substitution pattern of siloxyalkynes can be well tolerated (Table 3, entries 5–10). It is also interesting to note that ynamines are known to react with quinolinium and isoquinolinium salts to produce structurally different products under thermal conditions,4 which points to a unique role of silver(I) salt in promoting the formation of the observed aromatic products.…”
Section: Initial Reaction Optimizationmentioning
confidence: 99%
“…This study also demonstrated that a broad substitution pattern of siloxyalkynes can be well tolerated (Table 3, entries 5–10). It is also interesting to note that ynamines are known to react with quinolinium and isoquinolinium salts to produce structurally different products under thermal conditions,4 which points to a unique role of silver(I) salt in promoting the formation of the observed aromatic products.…”
Section: Initial Reaction Optimizationmentioning
confidence: 99%
“…This study also demonstrated that broad substitution pattern of siloxy alkynes can be well tolerated (Table 3, entries 5-10). It is also interesting to note that ynamines are known to react with quinolinium and isoquinolinium salts to produce structurally different products under thermal conditions, [4] which points to a unique role of silver(I) salt in promoting the formation of the observed aromatic products.…”
mentioning
confidence: 99%